QTL Mapping Combined With Comparative Analyses Identified Candidate Genes for Reduced Shattering in Setaria italica - Odonkor, Sandra; Choi, Soyeon; Chakraborty, Debkanta; Martinez-Bello, Liliam; Wang, Xuewen; Bahri, Bochra A.; Tenaillon, Maud I.; Panaud, Olivier; Devos, Katrien M. (Frontiers in Plant Science, 2018)
Setaria (L.) P. Beauv is a genus of grasses that belongs to the Poaceae (grass) family, subfamily Panicoideae. Two members of the Setaria genus, S. italica (foxtail millet) and S. viridis (green foxtail), have been studied extensively over the past few years as model species for C4-photosynthesis and to facilitate genome studies in complex Panicoid bioenergy grasses. We exploited the available genetic and genomic resources for S. italica and its wild progenitor, S. viridis, to study the genetic bases of seed shattering. Reduced shattering is a key trait that underwent positive selection during domestication. Phenotyping of F2:3 and recombinant inbred line (RIL) populations generated from a cross between S. italica accession B100 and S. viridis accession A10 identified the presence of additive main effect quantitative trait loci (QTL) on chromosomes V and IX. As expected, enhanced seed shattering was contributed by the wild S. viridis. Comparative analyses pinpointed Sh1 and qSH1, two shattering genes previously identified in sorghum and rice, as potentially underlying the QTL on Setaria chromosomes IX and V, respectively. The Sh1 allele in S. italica was shown to carry a PIF/Harbinger MITE in exon 2, which gave rise to an alternatively spliced transcript that lacked exon 2. This MITE was universally present in S. italica accessions around the world and absent from the S. viridis germplasm tested, strongly suggesting a single origin of foxtail millet domestication. The qSH1 gene carried two MITEs in the 5’UTR. Presence of one or both MITEs was strongly associated with cultivated germplasm. If the MITE insertion(s) in qSH1 played a role in reducing shattering in S. italica accessions, selection for the variants likely occurred after the domestication of foxtail millet.